Distribution of Macrozoobentos In The Estuary of Seletreng River, Situbondo District - Lukman Al Hakim; Hariyadi Hariyadi; Anis Zubaidah (IJOTA (Indonesian Journal of Tropical Aquatic), 2020)
The estuary of the Seletreng river is located in the Banyuglugur area of the Situbondo Regency and is directly adjacent to the shrimp pond area. The estuary of this river is widely used by local residents to look for fish, crabs. The existence of shrimp ponds near the mouth of this river has made many changes to the surrounding ecosystem. The purpose of this study is to determine the diversity index of macrozoobenthos and to determine the uniformity of macrozoobenthos. This research was conducted in February-March 2019, located in the waters of the mouth of the Seletreng Banyuglugur river, Situbondo district. Uses 5 stations with 3 repetitions. The diversity index value at the five stations, namely at station 1 is at a value of 0.66 which is categorized as low, at station 2 it is 0.36, at station 3 is 0.53, at station 4 is 0.65, at station 5 is 0, 25 wherefrom all stations the diversity index value is less than 1 and categorized as low diversity. The uniformity index value at the five stations, namely at station 1 is at a value of 0.37, at station 2 is 0.18, at station 3 is 0.24, at station 4 is 0.40, at station 5 is 0.12 wherefrom all stations diversity index value less than 1 and categorized on uniformity depressed.